SPECT/CT in addition to subtraction parathyroid scintigraphy in hyperparathyroidism: diagnostic performance in a cohort of predominantly end-stage renal disease patients - Worachart Jitrapinate; Yutapong Raruenrom; Nantaporn Wongsurawat; Prakasit Sa-Ngiamwibool; Daris Theerakulpisut (EJNMMI Research)
Abstract Background SPECT/CT has been well established as a valuable technique in nuclear medicine parathyroid imaging, but most previous studies were done in patients with primary hyperparathyroidism. In this retrospective study, we examined the diagnostic performance of [99mTc]NaTcO4 / [99mTc]Tc-MIBI planar subtraction parathyroid scintigraphy (PS), SPECT/CT, and a combination of the two in a patient cohort consisting of mostly end-stage renal disease (ESRD) patients with secondary or tertiary hyperparathyroidism, using histopathological results as the reference standard. Results Among 116 patients included, 98 (84.5%) had ESRD. The overall sensitivity of subtraction PS, SPECT/CT and combined interpretation was 69% (95% confidence interval: 64–73%), 67% (61–72%), and 79% (74–84%), while the specificity was 68% (59–76%), 71% (61–80%), and 60% (50–70%), respectively. For patients without ESRD with predominantly primary hyperparathyroidism, the sensitivity was 93% (70–99%), 89% (57–98%), and 100% (70–100%), and the specificity was 88% (76–94%), 87% (71–95%), and 84% (67–93%), respectively. For those with ESRD with predominantly tertiary and secondary hyperparathyroidism, the sensitivity was 67% (62–72%), 66% (60–71%), 78% (73–83%), and the specificity was 55% (42–67%), 57% (43–70%), and 43% (30–58%), respectively. Conclusion SPECT/CT was not superior to subtraction PS in ESRD patients with hyperparathyroidism. Combining these two techniques improves sensitivity, but likely with the expense of reduction in specificity. Both planar subtraction PS and SPECT/CT have suboptimal diagnostic performance in ESRD patients compared with non-ESRD patients where these techniques provide impressive sensitivity and specificity.